Long non-coding RNA FAM83A antisense RNA 1 (lncRNA FAM83A-AS1) targets microRNA-141-3p to regulate lung adenocarcinoma cell proliferation, migration, invasion, and epithelial-mesenchymal transition progression. Issue 3 (1st March 2022) - Huang, Hongyu; Yang, Chuyi; Zhang, Qichen; Zhuo, Ting; Li, Xiaohong; Li, Nijiao; Zhu, Lu; Luo, Chenyang; Gan, Jinyan; Wu, Yanbin
ABSTRACT: The current paper investigates how long non-coding RNA (lncRNA) FAM83A antisense RNA 1 (lncRNA FAM83A-AS1) affected the epithelial-mesenchymal transformation (EMT), growth, invasion and migration of lung adenocarcinoma (LUAD) via targeting miRNA-141-3p. The GEPIA and ENCORI databases were used to analyze differences in lncRNA FAM83A-AS1 levels within LUAD samples. FAM83A-AS1 and miR-141-3p levels were assessed using qRT-PCR among 30 LUAD samples and surrounding normal tissues. In addition, we analyzed how FAM83A-AS1 affected proliferation, invasion, migration, and EMT processes of LUAD cells by targeting miR-141-3p through EdU, CCK-8 assay, scratch assay, transwell migration and invasion assay, immunofluorescence (IF) staining and WB assay. MicroRNAs targeting FAM83A-AS1 were screened using AnnoLnc2 and identified by RT-qPCR. Dual-luciferase assays were utilized to evaluate the connection between FAM83A-AS1 and miR-141-3p. FAM83A-AS1 expression was remarkably raised in lung cancer cells and tissue samples; however, miR-141-3p level markedly reduced relative to healthy samples. FAM83A-AS1 silencing suppressed EMT, growth, invasion and migration of LUAD cells. MiR-141-3p was the possible FAM83A-AS1 binding target negatively associated with FAM83A-AS1. The miR-141-3p inhibitor partly abolished the FAM83A-AS1 knockdown-induced inhibition on EMT, cell growth, invasion and migration in LUAD cells. In addition, miR-141-3p down-regulation abolished the inhibition of E-box-bound zinc finger protein 1 and 2 protein production following FAM83A-AS1 knockdown. According to our results, FAM83A-AS1/miR-141-3p axis plays an important role in LUAD occurrence and development. FAM83A-AS1 sponged miR-141-3p to down-regulate the level of the latter within LUAD and thereby encouraging LUAD development and suggesting a possible novel therapeutic approach for LUAD. Graphical abstract: uf0001